From Peripheral to Integral? A Digital-Born Journalism Not for Profit in a Time of Crises - Hermida, Alfred (2019)
This article explores the role of peripheral actors in the production and circulation of journalism through the case study of a North American not-for-profit digital-born journalism organization, The Conversation Canada. Much of the research on peripheral actors has examined individual actors, focusing on questions of identity such as who is a journalist as opposed to emergent and complex institutions with multiple interventions in a time of field transition. Our study explores the role of what we term a ‘complex peripheral actor,’ a journalism actor that may operate across individual, organizational, and network levels, and is active across multiple domains of the journalistic process, including production, publication, and dissemination. This lens is relevant to the North American journalism landscape as digitalization has seen increasing interest in and growth of complex and contested peripheral actors, such as Google, Facebook, and Apple News. Results of this case study point to increasing recognition of The Conversation Canada as a legitimate journalism actor indicated by growing demand for its content from legacy journalism organizations experiencing increasing market pressures in Canada, in addition to demand from a growing number of peripheral journalism actors. We argue that complex peripheral actors are benefitting from changes occurring across the media landscape from economic decline to demand for free journalism content, as well as the proliferation of multiple journalisms.